Relationship of Glycated Haemoglobin with Lipid Profile among Patients with Type 2 Diabetes Mellitus - Samdani, Tasrina Shamnaz; Mitra, Palash; Rahim, Muhammad Abdur (BIRDEM Medical Journal, 2017)
Background: Glycated hemoglobin (HbA1c) is widely used as an index of mean glycaemia, a measure of risk for the development of diabetic complications and a measure of the quality of diabetes care. Patients with type 2 diabetes have an increased prevalence of dyslipidemia. Treatment of dyslipidaemia improves cardiovascular outcomes. The aim of this study was to determine the impact of glycemic control on lipid profile. Methods: This cross-sectional study was conducted among 300 type 2 diabetic patients admitted in BIRDEM General Hospital from November 2013 to April 2015. Fasting blood samples were collected and different lipid fractions along with fasting blood glucose and HbA1c were estimated. Pearsons correlation test was applied to evaluate the correlation between HbA1c and components of lipid profile. Results: The mean value of total cholesterol (TC), triglyceride (TG), low density lipoprotein-cholesterol (LDLC), fasting blood glucose (FBG) and HbA1c were higher and high density lipoprotein-cholesterol (HDL-C) was lower in females when compared with these values for males. HbA1c had significant positive correlation with LDL-C (p=0.045) and negative correlation with HDL-C (p=0.024). Serum lipid profile and glycaemic controls were significantly (p=0.000) better in older age group (age ? 50 years). Conclusions: Significant positive correlation of HbA1c with lipid profiles specially LDL-C suggested that HbA1c can also be used as predictor of dyslipidemia in addition to glycemic control. Birdem Med J 2017; 7(1): 43-47